Sweet Rewards: An Exercise to Demonstrate Process Theories of Motivation. (March 2019) - Holbrook, Robert L.; Chappell, David
Motivation is a fundamental component in management and organizational behavior courses. At the same time, it can be a complicated topic for teaching and learning due to the number of popular models and theories. The activity described here is a simple and fast way to illustrate the components of two of the most important and practical motivation theories—Equity Theory and Expectancy Theory. The impact of the activity will be realized the moment a disproportional reward is made. We outline implementation steps and provide an extensive list of questions to check students' understanding of motivation theories. We also provide additional resources (i.e., media suggestions, discussion slides) to enhance classroom presentations. This exercise is designed primarily for management and organizational behavior courses. It can be used effectively with a variety of audiences (i.e., undergraduate, graduate, executive).